2014
DOI: 10.1177/0363546514531551
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Findings in the Symptomatic Hips of Younger Retired National Football League Players

Abstract: This study demonstrated a high incidence of intra-articular pathologic lesions of the hip in a younger cohort of retired NFL players. The majority of players had bilateral hip pain. The most common finding was chondral lesions, followed by labral tears. Future research is needed to further elucidate incidence and treatment outcomes using prospective studies examining active and retired players with hip-related injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
(20 reference statements)
0
12
0
Order By: Relevance
“…There was limited evidence of a pooled labral tear prevalence of 92% (95% CI 29% to 100%) per hip from two (two MR)41 61 MRA studies, with moderate evidence of a pooled labral tear prevalence of 32% (95% CI 16% to 54%) from two (one MR and one LR)58 67 studies using MRI (online supplementary appendix 3 figure 1). The remaining two studies (one HR and one MR) reported a labral tear prevalence of 89%55 and 48%51 per hip, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was limited evidence of a pooled labral tear prevalence of 92% (95% CI 29% to 100%) per hip from two (two MR)41 61 MRA studies, with moderate evidence of a pooled labral tear prevalence of 32% (95% CI 16% to 54%) from two (one MR and one LR)58 67 studies using MRI (online supplementary appendix 3 figure 1). The remaining two studies (one HR and one MR) reported a labral tear prevalence of 89%55 and 48%51 per hip, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…One study (MR)41 reported a cartilage defect prevalence of 95% in participants with FAI. Three (one HR, one MR and one LR) of the remaining four studies used a combination of MRI and MRA (98%)55 and MRI in isolation (45% and 49%)51 58 to identify cartilage defects. The final study (MR)67 reported on acetabular (27%) and femoral cartilage defects (7%) in golfers with hip pain.…”
Section: Resultsmentioning
confidence: 99%
“…Cartilage lesions are frequently related to sports injuries, as shown in a recent study in younger retired National Football League players [81]. In that study, chondral lesions were found in 98% (54/55) of the players [81].…”
Section: Traumatic Cartilage Injuriesmentioning
confidence: 61%
“…In that study, chondral lesions were found in 98% (54/55) of the players [81]. Cartilage lesions were more frequent than labral tears or any other abnormality.…”
Section: Traumatic Cartilage Injuriesmentioning
confidence: 66%
“…Moreover, sports including repetitive hip flexion, such as soccer or ice-hockey, may cause chondrolabral damage to the hip joint and thereby pain in the hip and groin area [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%